Immersive Empathy: Assessing the Efficacy of Virtual Reality (VR) Simulations in Developing Cross-Cultural Competence in Higher Education - Ahmed Ali; Fadumo Ibrahim; Mohamed Ahmed (Yayasan Adra Karima Hubbi, 2025)
Background. In higher education, fostering cross-cultural competence is essential for preparing students to navigate a globally interconnected world. Traditional methods of teaching cultural understanding have often been limited by the constraints of classroom environments. Virtual Reality (VR) simulations present a promising tool for enhancing empathy and providing immersive, experiential learning opportunities. This research investigates the efficacy of VR simulations in developing cross-cultural competence among higher education students. Purpose. The study aims to assess whether VR-based experiences can effectively improve students' ability to understand and empathize with cultures different from their own. Method. A mixed-methods approach was employed, combining pre- and post-assessments of cross-cultural competence with qualitative feedback from participants. The sample consisted of 200 university students who engaged in a series of VR simulations designed to simulate interactions in diverse cultural contexts. Results. The results indicate a significant improvement in students' empathy levels and understanding of cultural nuances, as evidenced by both quantitative assessments and qualitative reflections. Conclusion. The study concludes that VR simulations offer a highly effective and engaging method for enhancing cross-cultural competence, providing an immersive platform for students to experience and reflect on cultural diversity in ways that traditional methods cannot replicate.